Analisis Pola Konsumsi Telur Ayam Ras oleh Rumah Tangga Peserta Program Keluarga Harapan di Kota Pekanbaru - Ramadhani, Anisa; Bakce, Djaimi; Novian, Novian (Universitas Galuh, 2026)
This study is motivated by the rising price of broiler eggs and the high dependency of low-income households in Pekanbaru City particularly those participating in the Program Keluarga Harapan on this commodity as their main source of animal protein. The research aims to examine the consumption patterns of broiler eggs among PKH beneficiary households based on household category, occupation type, and education level. A quantitative approach was employed using a survey method involving 315 PKH households across seven districts in Pekanbaru City, selected through a multistage sampling technique. The data were analyzed descriptively, and the results revealed variations in broiler egg consumption patterns according to household category, education level, and occupation. However, the overall consumption level remains below the recommended daily intake of 55 grams per capita per day, both on average and across household groups.